The Nexus between Social Factors, Basic Psychological Needs and Task-value of Tertiary EFL Learners: A Bangladeshi Perspective - Shurovi, Marzia (Theory and Practice of Second Language Acquisition, 2024)
This paper aims to explore the impacts of social factors and basic psychological needs of tertiary EFL learners on their task-value to learn English. Though ample studies have investigated EFL learners’ socio-economic status and basic psychological needs, there is a dearth of studies of their effects on their task value in English as a Foreign Language learning. Hence, this study has employed a quantitative research design with a questionnaire to collect data from 110 EFL tertiary learners of Dhaka, Bangladesh. A correlation using SPSS and path and mediation analyses using IBM SPSS AMOS were conducted to analyze the data. The results revealed a positive and significant correlation of learners’ task value with their social factor—school location and two basic psychological needs (BPN): factors-competence and relatedness. Fathers’ education among social factors and autonomy among BPN factors had the largest effects on task value. School location significantly influenced learners’ autonomy and competence. Both autonomy and competence in turn significantly and positively affected learners’ task value. Autonomy and competence also mediated in the relationship between learners’ school location and task value in the EFL context. In addition to adding new insights to the existing EFL achievement motivation literature, the paper also discusses the pedagogical implications of the findings.